1975
DOI: 10.1136/sti.51.3.198
|View full text |Cite
|
Sign up to set email alerts
|

Non-specific urethritis and the tetracyclines.

Abstract: Non-specific urethritis (NSU) is treated as an entity, yet it includes cases of urethral inflammation presumed to be related to the presence of probably several specific organisms. The effectiveness of the tetracycline group of antibiotics in comparison with other forms of treatment is not in doubt (Wilcox, 1972). In the present study we wish to remark upon the aetiology of NSU and to discover whether tetracycline treatment can assist us in understanding the nature of NSU, and also to comment on the best appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

1977
1977
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 57 publications
0
4
0
1
Order By: Relevance
“…It may be more helpful to try to distinguish the cases in which there is a marker-such as Chlamydia trachomatis, Trichomonas vaginalis, or the herpes simplex virus-or some other identifiable feature. In this way we may explain the apparently irreconcilable findings that led Weston (1965) to suggest that allergy may have an important aetiological role, Grimble and Amarasuriya (1975) to postulate mixed infections, and Evans (1977) We fail to see how these figures could be taken to 'incline the reader to caution' in accepting our results. Mr Simopoulos also chides us for not having used a placebo in the trial.…”
mentioning
confidence: 67%
“…It may be more helpful to try to distinguish the cases in which there is a marker-such as Chlamydia trachomatis, Trichomonas vaginalis, or the herpes simplex virus-or some other identifiable feature. In this way we may explain the apparently irreconcilable findings that led Weston (1965) to suggest that allergy may have an important aetiological role, Grimble and Amarasuriya (1975) to postulate mixed infections, and Evans (1977) We fail to see how these figures could be taken to 'incline the reader to caution' in accepting our results. Mr Simopoulos also chides us for not having used a placebo in the trial.…”
mentioning
confidence: 67%
“…Some authors have suggested that triple tetracycline is more effective than oxytetracycline in the treatment of NSU (Bhattacharyya and Morton, 1973), but this is disputed by other workers (Willcox, 1972;Grimble and Amarasuriya, 1975). These conflicting reports indicate that no good scientific evidence exists for the use of triple tetracycline in preference to tetracycline.…”
Section: Discussionmentioning
confidence: 99%
“…This longer period may have been because the patient was Chlamydiapositive or because it was considered that a better cure rate could be obtained. The latter possibility has been suggested by John (1971) but since disputed by several authors (Willcox, 1972;Helmy and Fowler, 1975;Grimble and Amarasuriya, 1975). There would appear to be no justification for prescribing tetracycline or oxytetracycline for more than five to seven days unless a clear diagnosis of chlamydial infection has been made.…”
Section: Discussionmentioning
confidence: 99%
“…76 In the same year a study based on patients at Guy's Hospital in London concluded that only 20 percent were "truly non-specific"; the remainder broke down as follows: chlamydia, 40 percent; mycoplasma, 20 percent; trichomoniasis, 15 percent; and candidiasis, 5 percent. 77 The diversity of diseases making up NSU remained a challenge and, according to Robbie Morton, a venereologist based in Sheffield, "In spite of much laboratory and other research, nonspecific genital infection continues to be the venereologist's most perplexing problem, clinically, diagnostically and therapeutically." 78 In 1978, Michael Adler, then at the Middlesex Hospital and following a review of the diagnosis and reporting of NSU, wrote, "It is extremely unsatisfactory that when the disease is discussed, described, diagnosed, and notified no accepted criteria are in existence" and "The commonest diagnosis made in STD clinics [is] the one with the least uniformity."…”
Section: Gonorrhea and Nongonococcal Urethritis 1900-1945mentioning
confidence: 99%